Removal Analysis of Residual Photoresist Particles Based on Surface Topography Affected by Exposure Times of Ultraviolet and Developer Solution - Park, Jinwon (Langmuir : the ACS journal of surfaces and colloids, 2022)
Particle removal from the surface of a substrate has been an issue in numerous fields for a long time. In semiconductor processes, for instance, the formation of clean surfaces by removing photoresist (PR) must be followed in order to create neat patterns. Although PR removal has been intensively investigated recently, little is known about how ultraviolet (UV) and developer solutions alter the PR resin (and in what manner) near the surface. While varying the exposure times of UV and developer solution, we investigated the topographic changes on the surfaces of PR resin films and particles. The measured surface properties were then correlated with the detachment force determined using films, and eventually with the residual PR particle removal percentages obtained in a microchannel. Using a positive PR and a base developer solution, we demonstrated that UV causes the surface of PR resin to become hydrophilic and wavy, whereas the developer solution produces a surface with a larger degree of roughness by swelling and partially dissolving the resin. Ultimately, the increased roughness decreased the effective contact area between PR resins, hence decreasing the detachment force and increasing the particle removal percentages. We anticipate that our findings will help understand residual particle issues, particularly on the removal mechanism of PR resins based on surface topography